N2O–Assisted Siphon Foaming of Modified Galactoglucomannans With Cellulose Nanofibers - Nypelö, Tiina; Fredriksson, Jessica; Arumughan, Vishnu; Larsson, Emanuel; Hall, Stephen A.; Larsson, Anette (Frontiers in Chemical Engineering, 2021)
Foaming of most bio-based polymers is challenged by low pore formation and foam stability. At the same time, the unfolding bio-based materials utilization for circular economy demands for low-density materials from renewable raw materials that are easily processable. We focus here on cellulose nanofibril (CNF) foams where foaming is facilitated with wood-based hemicelluloses, galactoglucomannans (GGM). Interfacial activity of the galactoglucomannan is modulated via modification of the molecule’s amphiphilicity, where the surface tension decreased from approximately 70 to 30 mN m-1 for unmodified and modified GGM, respectively. The chemical modification of the galactoglucomannans by substitution with butyl glycidyl ether increased the molecule hydrophobicity and interaction with the nanocellulose component. The highest specific foam volume using 1 wt% CNF was achieved when modified GGM was added (3.1 ml g-1), compared to unmodified GGM with CNF (2.1 ml g-1). It was also shown that the lost foam volume at 15 min decreased dramatically when CNF was added to both modified and unmodified GGM (approximately 30%) compared to >95% lost volume for the hemicelluloses without CNF. This suggests that the altered hydrophobicity facilitated increased foam formation when the additive was incorporated in CNF suspension and foamed with nitrous oxide (N2O). Thus, the hydrophobic character of the modified galactoglucomannan was a necessity for foam formation and stability while the cellulose fibrils were needed for generating a self-standing foam structure.